O ensino de algoritmos no ensino médio: por que não? - Leal, Willian da Silva (2009)
This research investigates, through a strategy of teaching practice, the possibility of teaching algorithms in high school, by a workshop with teaching activities, indicating the possibility of developing it through an extra class and extra curriculum activity, having as reference the application of algorithms, using concepts associated with the Theory of Graphs and Mathematical Modeling technique. This activity was developed with students from federal public school in Duque de Caxias a and a private school located in the center of Duque de Caxias, where some facilities and difficulties have been demonstrated by the students in the process of knowledge construction, integrating data from a literature search and the results obtained in the proposed activity, and producing, in this way, a study on a proposed reason of teaching and learning algorithms and hence the mathematical modeling. The development of algorithm thought, mathematical modeling techniques and the concepts of discreet mathematics is essential in the development of mathematics, then science and technology. In a computer world where we live in, it is necessary the individual’s cognitive development. The introduction, in education, would give citizens the ability to live actively in a world based on sequential procedures and interconnected in a logical way which characterizes the algorithm.